The Axis Mundi Stupa Tradition from East Asia to Europe - Khetani, Katalin Puskas (Technium Sustainability, 2024)
Numerous studies have started to explore a new research avenue on stupa architecture interpretations in the last century. This novel approach introduces symbolism into the potential passages of investigation and ways of acquiring new information. This fresh perspective opens new paths for the academic community to look at existing data from a unique and different angle, potentially bringing correspondingly formerly unknown and untouched knowledge to the surface. Following the symbolic stupa architecture approach, the purpose of this paper is to attempt to look at current information from a different perspective, in a larger geographic area and cultural context, trying to shed some lite on some potentially relevant facts and associations, that may help to ask questions in a possibly more articulate and refined way in search of the answers.